Chlorophyll fluorescence, Orbital and Photosynthesis: practical activities integrating concepts of Chemistry, Physics and Biology - Elgion Lucio da Silva Loreto (Journal of Biochemistry Education, 2013)
These laboratory activities explore the relationship between the reserve of energy that occur during photosynthesis and the chlorophyll fluorescence emission when in solution as opposed to absence of fluorescence when the chlorophyll are in intact chloroplasts. This proposal can be used as short demo or as  activities with longer duration, to show chlorophyll's properties associated with the photosynthesis. The materials proposed for the implementation of the activities are simple, and possible to building it by the students, enabling the development of various skills and experimental proposals. The protocols are based on observations and record key questions to continue the execution. During the activities, questions promotes pauses for moments of reflection and review of concepts. At the end are presented and discussed proposals for development of interdisciplinary projects.